O comentário no site www.papodehomem.com.br: reflexão sobre prática de escrita e leitura, gênero discursivo e contínuo dialógico - Andrade, Felipe Sousa de [UNESP] (2016)
The paper that is presenteda aims to reflect on the practice of reading and writing on the internet, particulary in www.papodehomem.com.br webpage. From these practices, we also reflect on the typical comment as discursive genre and as a statement that has a dialogical continuity with the other statements. These intentions are given by the fact that we found on the site stylistic peculiarities, unique compositional and thematic on the comments: commentators not only commented on the text in a brief and casual way; they complemented the commented text. They supplemented from similar processes and the computer support particular processes. From a listed readback, we selected five tutorials that peculiarities are gaven in more apparent way. Are these tutorials: Como engraxar e dar brilho aos seus sapatos, passo-a-passo; Como fazer ceviche, passo-a-passo; Como fazer feijão, passo-a-passo; Aprenda a assoviar como seu avô; Receita de hambúrguer do MEATS! Como fazer o hambúrguer mais matador de todos. Our readback is through ideas proposed by the Bakhtin circle. Notions of speech genres, finishing and responsible act are basic and fundamental to understand the dialogue that exists between the statements and the proposed continuum that we propose.